Personal loan preference of bank borrowers: A conjoint analysis - Salimaco, Philip; Murcia, John Vianne (Business and Organization Studies e-Journal, 2024)
In Mati City’s financial sector, personal loans play a crucial role in addressing needs like education and home improvements. This study uses conjoint analysis to examine bank borrowers' preferences, identifying key factors that influence loan choices and offering insights for banks to optimize their products and marketing strategies. Given the city's evolving economy, understanding localized borrower preferences is essential. The study presents respondents with hypothetical loan scenarios featuring attributes such as collateral, loan period, interest rates, payment modes, and income requirements. This helps determine the relative importance of these factors in borrower decision-making. Findings reveal variations in how borrowers prioritize loan attributes, highlighting unique local considerations. The study also segments borrowers based on preference patterns, enabling banks to develop tailored financial products. Additionally, it emphasizes trust-building, community engagement, and financial education to enhance borrower awareness and literacy. Banks can design personalized loan offerings and customer-centric strategies, enhancing financial inclusion and economic growth by leveraging these insights